(untitled) (Jurnal Teknologi (Sciences & Engineering), 2024)
Solar stills have become a viable and environmentally responsible method of water purification in the context of tackling the urgent worldwide issue of water scarcity. Solar stills are a practical solution for areas with poor access to clean drinking water since they use the sun's limitless energy to filter contaminants from water. Standard solar still models have been used for this purpose, however their effectiveness and output quality frequently fell short of expectations. Consequently, there is a compelling need to investigate novel designs and technologies in order to improve the functionality of solar stills and the quality of the filtered water. This study examines solar stills as a means of removing contaminants from water within the context of water purification utilizing solar energy. The study specifically highlights a pyramid solar still's inventive design and evaluation because it deviates from regularly used standard models. This pyramid solar still has been designed in a special way, and a thermoelectric system has also been added to improve performance. Furthermore, real-time monitoring of critical water parameters is made possible by the integration of sensors like the DHT11. A pH sensor, a water level sensor, and an Arduino Uno microcontroller are used to provide this real-time monitoring, which provides ongoing information on the purifying process. A heating plate has been added to the pyramid solar still to improve the evaporation process and increase efficiency.